2022
DOI: 10.1111/trf.16794
|View full text |Cite
|
Sign up to set email alerts
|

Autotransfusion of vaginally shed blood as a novel therapy in obstetric hemorrhage: A case series

Abstract: Objective To report maternal outcomes in a cohort of women who received autotransfusion of vaginally shed blood and to describe the feasibility of blood collection and cell salvage processing at the time of vaginal hemorrhage. Study Design and Methods We conducted a retrospective case series of patients who received autotransfusion of vaginally shed blood at the time of obstetric hemorrhage from January 2014 to August 2020. Maternal data and cell salvage utilization characteristics were abstracted from the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…12 Studies describing the clinical application of cell salvage technology during vaginal obstetric hemorrhage are restricted to small observational case series. 13,14 These case series demonstrate the feasibility of blood collection and autotransfusion during vaginal obstetric hemorrhage. Prior studies, however, fail to address important maternal outcomes such as impact on hemoglobin, allogenic blood transfusion, or maternal morbidity in the context of unexposed controls.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…12 Studies describing the clinical application of cell salvage technology during vaginal obstetric hemorrhage are restricted to small observational case series. 13,14 These case series demonstrate the feasibility of blood collection and autotransfusion during vaginal obstetric hemorrhage. Prior studies, however, fail to address important maternal outcomes such as impact on hemoglobin, allogenic blood transfusion, or maternal morbidity in the context of unexposed controls.…”
Section: Introductionmentioning
confidence: 80%
“…Deliveries exposed to autotransfusion that were utilized for this analysis were previously described in a case series. 14 In the current analysis, the primary outcome is to compare exposed cases with a large, unexposed control cohort. All deliveries occurred between January 1, 2014 and August 1, 2020.…”
Section: Methodsmentioning
confidence: 99%
“…This is especially true for caesarean delivery. The use of cell salvage in spontaneous births is practiced only very sporadically [27,28].…”
Section: Key Pointsmentioning
confidence: 99%
“…In a recent publication, we reviewed 64 cases of autotransfusion of vaginally shed blood that occurred at our institution prior to initiation of a standardized protocol for blood collection and processing during vaginal obstetric hemorrhage 22 . We found that autotransfusion of vaginally shed blood was well tolerated and no serious adverse events were reported during administration.…”
Section: Outcomes In Cases With Autotransfusion Of Vaginally Shed Blo...mentioning
confidence: 99%